The Relationship Between Social Stigma And The Incidence Of Depression In Pulmonary Tuberculosis (Tb) Patients: A Cross-Sectional Study - Sri Ayu Rahayu Paneo; Zakariyati Zakariyati; Hasbullah Hasbullah; Ardwita Insani Bachtiar (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
Background: One of the infectious diseases is tuberculosis (TB). TB is an infectious disease that causes high rates of morbidity and even death. TB is very dangerous and requires various efforts to overcome it; therefore, preventive measures are needed for those who are already infected. It is important to increase public awareness about how TB is transmitted and prevented so that its spread can be minimized. Based on data from Riskesdas 2018, there were 1,017,290 cases of pulmonary TB. Objective: To determine the relationship between stigma and the incidence of depression in pulmonary tuberculosis patients in the working area of Mamajang Health Center, Makassar. Method: The method used was Spearman correlation, which is descriptive research using a quantitative design with a cross-sectional approach. The sampling technique used was total sampling with a population of 83. Results: There was a relationship between stigma and the incidence of depression in pulmonary tuberculosis patients with p-value 0.025. Conclusion: There is a relationship between stigma and the incidence of depression in pulmonary tuberculosis patients in the working area of Mamajang Health Center, Makassar. This study aims to provide insight for health workers and the government to develop better intervention programs in treating TB patients, both physically and psychologically, with a focus on reducing social stigma towards them.